2019
DOI: 10.1088/1757-899x/624/1/012030
|View full text |Cite
|
Sign up to set email alerts
|

Milling cutter condition monitoring using machine learning approach

Abstract: The cutting tool condition drives the economy of machining processes in manufacturing industry. The failures in cutting tool are unbearable and affect the drive of machine tool which reduces life. Hence it necessitates reducing power consumption using monitoring cutting tool condition and hence requires an efficient supervision to monitor and predict faults. Simply stated, the condition which curtails cutting tool life highlighted before it turns into a tool wear, breakage and failure. This ensures optimized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…In tune with this, the accelerometer needs to be placed closer to the posting of a tool. A vibration with a component in the direction of cutting is best responsive to the tool wear as compared to the others, for that reason the accelerometer was [3][4][5]. The data logger is developed using a microcontroller Arduino ATmega2560 and a computer for acquiring, conditioning, processing and storing the data from the accelerometer.…”
Section: Experimentation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…In tune with this, the accelerometer needs to be placed closer to the posting of a tool. A vibration with a component in the direction of cutting is best responsive to the tool wear as compared to the others, for that reason the accelerometer was [3][4][5]. The data logger is developed using a microcontroller Arduino ATmega2560 and a computer for acquiring, conditioning, processing and storing the data from the accelerometer.…”
Section: Experimentation Detailsmentioning
confidence: 99%
“…Cutting may edge itself individual might be dulling of very fast without any this effect manifesting itself before that itself, those things are not considered when dealing with the gradual phenomenon of wear this takes place very gradually. This is because the tool deteriorates quality when it is being put to use where the chip is rubbing against the rake surface while moving and also applying a considerable amount of force very frequently in the order of hundreds of neutrons [3][4][5]. A Tool Condition Monitoring (TCM) is a predictive maintenance system used for mechanical systems or machine tools that monitor the condition of a cutting tool.…”
Section: Introductionmentioning
confidence: 99%
“…The index was analyzed using the counter-propagative neural net. Recently, Patange et al [ 28 ] suggested an ML approach to diagnose the condition of a milling cutter. Relevant features were selected from a decision tree and for several tool conditions and classified using a random forest tree algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Different modelling techniques (such as artificial neural networks (ANNs), deep learning (DL), machine learning (ML), etc.) have been studied to monitor tool conditions, reduce cutting power consumption and increase energetic efficiency [26][27][28][29][30][31]. Tiryaki et al employed artificial neural networks to minimize the surface roughness and power consumption of wood abrasive machining processes.…”
Section: Introductionmentioning
confidence: 99%